2016
DOI: 10.1164/rccm.201506-1122oc
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Immunoproteasome Function by Cigarette Smoke and in Chronic Obstructive Pulmonary Disease

Abstract: We here show that the activity of the immunoproteasome is impaired by cigarette smoke resulting in reduced MHC I antigen presentation. Regulation of immunoproteasome function by cigarette smoke may thus alter adaptive immune responses and add to prolonged infections and exacerbations in COPD and IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 52 publications
4
44
0
Order By: Relevance
“…Further dysregulation of macrophage function in COPD was documented by significant downregulation of molecules associated with antigen presentation, especially MHC class I. This finding is in accordance with previous studies linking down-regulation of surface MHC class I in COPD with impaired immunoproteasome activity (Hodge et al, 2011;Kammerl et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Further dysregulation of macrophage function in COPD was documented by significant downregulation of molecules associated with antigen presentation, especially MHC class I. This finding is in accordance with previous studies linking down-regulation of surface MHC class I in COPD with impaired immunoproteasome activity (Hodge et al, 2011;Kammerl et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…COPD is a major cause of morbidity and mortality globally, and knowledge about its pathogenesis has increased substantially over the past decade (9,10). The primary risk factor for COPD is prolonged cigarette smoking (11). Another risk factor for COPD is chronic environmental exposure to toxic atmospheric pollutants, including PM (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…For example, using both nonselective and subunit-selective ABPs, Kammerl et al observed a reduction in both immunoproteasome activity and MHC class I antigen presentation in response to cigarette smoke. As immunoproteasome activity is a ratelimiting step for MHC class I antigen presentation, the authors speculated that cigarette smoke-impaired immunoproteasome function reduces MHC I-driven immune responses, making smokers more susceptible to viral lung infections [64]. ABP experiments have also suggested a role for the proteasome in epithelialmesenchymal transition (EMT), an important developmental process that is also associated with metastasis [65].…”
Section: Profiling Proteasome Activity Across Different Conditions Ormentioning
confidence: 99%